Stories of Struggle : The Clash over Civil Rights in South Carolina - Brinson, Claudia Smith (Book collections on Project MUSE., 2020)
"The end of desegregation and the attainment of civil rights for South Carolina's African American community from the 1940s through the 1960s was a long and arduous struggle. Enduring lynchings, death threats, bombs, robed Klansmen, burning crosses, whippings, beatings, arson, and venemous hatred, African Americans from Upstate to the Lowcountry displayed astonishing courage, devotion, and commitment to gain equality. This book tells stories of those struggles. For the past fifteen years South Carolina journalist Claudia Smith Brinson has researched the history of civil rights in the Palmetto State and interviewed dozens of civil rights activists who risked their lives to make their communities better places: fair, equal, democratic, and respectful of all human beings. Many of these individuals had never told their stories-to anyone. These are stories of petitioning, preaching, picketing, boycotting, marching, and holding sit-ins at stores, libraries, parks, and beaches. Brinson focuses on five case studies, reflecting individuals and actions that changed the landscape of civil rights in South Carolina but also reverberated throughout the South: the legal strategies of James Myles Hinton, Sr., the president of the South Conference of Branches of the NAACP in the 1940s and 50s; Joseph Armstrong Delaine and others involved in the Summerton's Briggs v. Elliott case in the early 1950s that led to the historic Brown v. Board of Education decision; Cecil Augustus Ivory, and the Freedom Riders in Rock Hill in 1960; the sit-ins that same year in Rock Hill, Orangeburg, Denmark, and Columbia, in which thousands of African American studies were arrested and jailed; and the 1969 hospital strikes in Charleston at Medical College Hospital and Charleston County Hospital, during which dozens of women played key roles. And while these are stories from South Carolina's past, the journey to equality never ends--as recently as 2014 the SC Supreme Court, in Abbeville II, ruled that the state had failed in its constitutional duty to provide a minimally adequate education--but provided no remedy. The struggle endures"--